Pengaruh Latihan Kecepatan Reaksi Terhadap Kecepatan Tendangan Mawashi Geri Pada Atlet Kumite Senior FORKI Maluku - salampessy, George J william; syaranmual, Jusak; solissa, Jonas (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2023)
ABSTRAK This research aims to determine there is an effect of reaction speed training on speed mawashi geri kick in senior Karate kumite athletes Maluku. This is an experimental research, where the writer wants to know the effect of Reaction Speed training on mawashi geri kick . The method used in this research is a field experiment method. The population used as the sample in this research amounted to 15 people, the variables is consisted of independent variables, Reaction Speed exercise using the indicators, One footed hop, Icky shuffle, Hip twist, Cross step reaction, Cone drill foot touch, Traffic light kick and the dependent variable mawashi geri speed kick indicator . The instruments are measurement instruments or test instruments and treatment instruments or training instruments. Based on the results and the measurement test obtained and statistical formulas, it can be concluded that the mawashi geri kick speed in FORKI Maluku senior Karate kumite athletes can be increased through reaction speed training.